Drinking Water Filter from Rice Husk Ash - Pattarith, Kongsak (Asian Journal of Chemistry, 2014)
The objective of this study was to prepare water filtering material from rice husk ash. The material was obtained by dissolving rice husk ash in sodium hydroxide solution and neutralized with HCl. The chemical composition of material was SiO2, Al2O3, Fe2O3 and Na2O in the values of 98.50, 0.49, 0.04 and 0.13 %, respectively. The morphology of material was undefined solid with BET surface area of 245.98 m2/g, average porosity of 13.38 nm and total pore volume of 0.76 cm3/g. The material was evaluated its filtration efficiency. The filter cartridge with 1.5 cm diameter and 9 cm long was made from 5 g of material and was assemble to a water filtering model. The filter capacity for water was up to 3 L and filtrated water was determined its quality index. Water quality parameters of the filtrate such as conductivity, turbidity, total dissolved solids and total hardness were lowered by 10.13, 94.72, 5.68 and 13.08 %, respectively, of the prior treated water.